Meningkatkan Profitabilitas Dengan Menerapkan Islamic Corporate Identity (Studi Pada Bank Umum Syariah di Indonesia Tahun 2014-2017) - Purwanto Purwanto (Institut Agama Islam Negeri Madura, 2019)
It is important for Islamic banking to provide information to the public that Islamic banking has an identity that is different from conventional banking. An important Islamic Corporate Identity for sharia banking is because it is one of the information for customers to use Islamic bank products, so the better the implementation of Islamic Corporate Identity, the more opportunities for Islamic banking to get investors and ultimately to increase profits. The purpose of this study is to find out how Islamic Corporate Identity influences profitability. This research was conducted on 12 Islamic public banks for the period 2014-2017. The data analysis technique used is panel data regression. From the results of panel data regression analysis, the results show that the Islamic Corporate Indentity variable in Islamic Commercial Banks in Indonesia in 2014-2017 has a positive significant effect on Profitability, this can be seen from the Prob value of 0.0045> 0.05. Thus the better the Islamic Corporate Indentity in Islamic Commercial Banks is the profitability of the bank.[Penting bagi perbankan syariah untuk memberikan informasi pada masyarakat bahwa perbankan syariah memiliki identitas yang berbeda dengan perbankan konvensional. Islamic Corporate Identity penting bagi perbankan syariah karena menjadi salah satu informasi untuk nasabah untuk menggunakan produk bank syariah, sehingga semakin baik penerapan Islamic Corporate Identity maka semakin banyak kesempatan bagi perbankan syariah untuk mendapatkan investor dan pada akhirnya dapat meningkatkan keuntungannya. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pengaruh Islamic Corporate Identity terhadap profitabilitas. Penelitian ini dilakukan terhadap 12 bank umum syariah periode 2014-2017. Teknik analisis data yang digunakan adalah regresi data panel. Dari hasil analisis regresi data panel diperoleh hasil bahwa variabel Islamic Corporate Indentity pada Bank Umum Syariah di Indonesia tahun 2014-2017 berpengaruh signifikan positif terhadap Profitabilitas (ROA) hal ini dapat dilihat dari nilai Prob 0,0045 > 0,05. Dengan demikian semakin baik Islamic Corporate Indentity pada Bank Umum Syariah maka profitabilitas bank.]